CAVE-THERAPY AS A KIND OF MEDICAL TOURISM (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
Cave-treatment has been widely spread in the world and is based on underground mineral and warm springs, different kinds of salts and other natural resources. People have been interested in it for centuries, but it was put in modern basis some decades ago. Cave-therapy is considered to beboth health and tourism. Cave-treatment motivates the health protection, the development of some kinds of tourism, the protection of natural monuments, the establishment of protected areas.
Keywords: cave-treatment; cave-therapy; medical tourism; balenotherapia; hydroteraphy